Social media marketing strategy adaptation into Chinese market. : Perspective of Finnish companies. - Elonen, Miia (My University, 2019)
By being one of the fastest growing economies China have allured Finnish companies to operate in China. Chinese market is different in many aspects, especially with their social media environment. Social media marketing is growing its importance for the marketers also in international context. Global borders have become smaller due to social media. This study aims to understand social media strategy adaptation of Finnish companies into Chinese market. How companies have organized their processes and companies overall international marketing strategy. Thesis is creating social media strategy framework to illustrate factors affecting the international marketing decision. Purpose is to explain the main factors related to the adaptation of social media strategy. Study evaluates how Finnish companies are adapting their social media strategy to China. Furthermore, study analyses the processes and the linkage of the social media strategy to the environment and the marketing strategy of the company. Empirical analysis was conducted through four interviews. All of the case companies had similar factors affecting on the social media strategy decisions. Main attributes affecting to marketing strategy were market knowledge, local partners and understanding the social media environment.
Keywords: social media, social media strategy, international marketing strategy, china; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business